2018
DOI: 10.1039/c7sc04396a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-dependent allosteric activation and inhibition on the same molecular scaffold: the copper sensor CopY from Streptococcus pneumoniae

Abstract: The dynamics and marginal stability of CopY enable allosteric activation of DNA binding by Zn(ii) and inhibition by Cu(i).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 54 publications
1
55
2
Order By: Relevance
“…hirae copper repressor and the upstream binding repeats are highly similar to S . pneumoniae (32, 33), and contain the 10-base sequence, E . hirae operators upon initial observation lacked the extended regions flanking this sequence in pneumococcus (Figure 1B) (22).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…hirae copper repressor and the upstream binding repeats are highly similar to S . pneumoniae (32, 33), and contain the 10-base sequence, E . hirae operators upon initial observation lacked the extended regions flanking this sequence in pneumococcus (Figure 1B) (22).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that CopY specifically bound to the cop operon operator in a sequence and metal specific manner as disrupting the operator bases or adding copper disrupted CopY binding, while adding manganese or iron had no detectable effect (32). These studies were done with only one full operator intact (32, 33). Thus, using an electric mobility shift assay (EMSA), we qualitatively tested CopY binding to DNA to the two-operator 61-base dsDNA fragment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations